INFORMATION ARCHITECTURE PADA APLIKASI E-COMMERCE: (STUDI KOMPARASI APLIKASI SHOPEE DAN TOKOPEDIA) - Sri Soedewi; Swasty, Wirania; Mustikawan, Arry; Naufalina, Fariha Eridani (Jurnal Bahasa Rupa, 2021)
Shopee and Tokopedia are popular marketplace applications in Indonesia that provide facilities for buying and selling goods online from various sellers or stores. Application is very influential for user convenience in the preparation of information architecture. The Information Architecture uses to compile the information. It is easier to understand for users when interacting with mobile applications. This study uses quantitative research methods by conducting observations, questionnaires distributing, and literature studies to analyzing the information architecture or structure, and knowing the user experience on the Shopee and Tokopedia applications using the tool Optimal Workshop. Information Architecture on Shopee and Tokopedia results is conducted based on the research and analysis, as a whole are good.